Frequent Mental health- and Addiction- related Emergency Department Visits: Perspectives from Healthcare Providers / Consultations fréquentes dans les services d’urgence pour des problèmes de santé mentale et de toxicomanie : le point de vue des prestataires de soins de santé - Tang, Kristy; Li, Hua (Canadian Journal of Emergency Nursing / Journal canadien des infirmières d’urgence, 2025)
Background: The rise in mental health- and addiction (MHA)-related emergency department (ED) visits has been recognized as a contributing factor to ED crises and increasing healthcare costs. While prior research has centred largely on patients’ perspectives, limited attention has been given to healthcare providers’ (HCPs’) insights. This study specifically explores HCPs’ perceptions of why patients with MHA issues frequently present to EDs.Methods: In this qualitative research, data collection involved semi-structured individual interviews. Thematic analysis approach was utilized in data analysis.Results: Six HCPs from diverse disciplines participated in this qualitative study. Four major themes emerged from the data analysis: (a) social determinants of mental health (a housing crisis and financial problems); (b) structural barriers (overstimulation and not a priority in ED, inadequate knowledge and training among HCPs, lack of withdrawal management facilities, stigma from HCPs, shortages of HCPs); (c) suggestions for prevention (more funding/ resources and early childhood education); and (d) HCPs’ response to working with patients (making a difference and rewarding).Conclusions: The study found that HCPs perceived low socioeconomic status and the limited availability of community mental health services and resources as key factors that contribute to frequent MHA-related ED visits. To understand the complex needs of individuals with MHA disorders better, all levels of government, community organizations, and HCPs, especially nurses, should collaborate to develop and implement effective interventions aimed at reducing frequent ED visits or returns related to MHA issues.